Information and authority: research on the mechanism of offspring's health information avoidance behavior - Dang, Qiong; Lin, Weiying; Li, Yifei (Frontiers in Public Health, 2025)
The health information shared by parents with their offspring, while originating from a place of care, has in practice led to resistance from the offspring. This has become a pressing issue in the field of health communication in contemporary China that requires urgent attention and resolution. Therefore, the study aims to explore how information factors and family factors together affect offspring's avoidance of health information shared by parents, within the context of the unique characteristics of social and family relationships in China. This study, based on the theoretical framework of the information acceptance model (IAM) and family communication patterns (FCPs), takes offspring under 30 years old as the research object, analyzes 1,505 valid questionnaires using SEM. The results revealed that within FCP, conversation orientation negatively impacts offspring's health information avoidance (HIA) behavior, while conformity orientation positively influences this behavior. An important finding is that parental authority and discourse power are the most significant determinants of offspring's HIA behavior. Additionally, the quality of health information and source credibility each positively affect offspring's perceived usefulness of the health information. Moreover, both perceived usefulness and attitude have a significant association with HIA behavior, with attitude mediating the relationship between perceived usefulness and HIA behavior. An interesting finding is that offspring's emotional responses and subjective attitudes play a critical role in the health information decision-making process. This study addresses the lack of focus on family communication patterns and information systems in health communication research and provides new insights for future studies.